1998
DOI: 10.1183/09031936.98.12061301
|View full text |Cite
|
Sign up to set email alerts
|

In vitro-induced human airway hyperresponsiveness to bradykinin

Abstract: aaAirway inflammation is one of the main features of asthma. It has been well established that people with respiratory infections may experience increased bronchial reactivity and impaired bronchial airflow [1,2]. Inhalation of endotoxin or lipopolysaccharide (LPS), a component of the outer cell wall of Gram-negative bacteria, has been reported to induce airway hyperresponsiveness in both normal [3] and asthmatic subjects [4]. The pathophysiological mechanisms underlying these changes after administration of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…In addition, delivery of an adenovirus expressing IL-1RA after sensitization and before airway antigen challenge alleviated AHR, pulmonary infiltration with eosinophils and neutrophils and decreased IL-5 levels [38], IL-1RA abrogated both the IL-5- and IgE-induced changes in airway smooth muscle responsiveness in asthma [39], whereas, in contrast, IL-1β and TNF-α increased airway smooth muscle response to various contractile agonists, e.g. methacholine [40]. Finally, IL-1β and TNF-α induce NF-ĸB-dependent CCL28 induction, a mucosal chemokine that attracts eosinophils and T cells via CCR3 and CCR10 [41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, delivery of an adenovirus expressing IL-1RA after sensitization and before airway antigen challenge alleviated AHR, pulmonary infiltration with eosinophils and neutrophils and decreased IL-5 levels [38], IL-1RA abrogated both the IL-5- and IgE-induced changes in airway smooth muscle responsiveness in asthma [39], whereas, in contrast, IL-1β and TNF-α increased airway smooth muscle response to various contractile agonists, e.g. methacholine [40]. Finally, IL-1β and TNF-α induce NF-ĸB-dependent CCL28 induction, a mucosal chemokine that attracts eosinophils and T cells via CCR3 and CCR10 [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that interleukin (IL)-1b induces AHR in several animal models [11][12][13]. In addition, BARCHASZ et al [14] described that IL1b causes AHR to the NK-1 tachykinin receptor agonist [Sar 9 ,Met(O 2 ) 11 ]-substance P (SP) in the human isolated bronchus.…”
mentioning
confidence: 99%
“…At the molecular level, several asthma triggers have been shown to increase ASM contractility ex vivo. For example, ASM contractility has been shown to be enhanced following prolong (at least 16 h) incubation with atopic serum (15,19,78,89,91,161,211,245,246), IgE immune complex (80,89,250) and exogenous asthma triggers such as the house dust mite allergen Der p 1 (82), the bacterial endotoxin lipopolysaccharide (LPS) (8,166,216,220) and the rhinovirus (serotype 16) (78,81) or the virus mimetic toll-like receptor (TLR)3 ligand polyinosinic polycytidylic acid (poly-IC) (8). Most of these studies assessed ASM contractility by measuring its force-generating capacity.…”
Section: Inflammatory Cells and Moleculesmentioning
confidence: 99%
“…The half-time of relaxation after short EFS-induced tetani has also been shown to increase (double) in ASM strips derived from dogs sensitized to ragweed (109). The effect of asthma triggers on ex vivo ASM contractility can be indirect; i.e., due to an autocrine loop of mediators that are produced by the ASM in response to asthma triggers (79,80,91,166). In vivo, the paracrine influence of other cells that are responsive to asthma triggers can also impact ASM contractility.…”
Section: Inflammatory Cells and Moleculesmentioning
confidence: 99%
See 1 more Smart Citation